If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(x + -75) = 0 Reorder the terms: -1(-75 + x) = 0 (-75 * -1 + x * -1) = 0 (75 + -1x) = 0 Solving 75 + -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-75' to each side of the equation. 75 + -75 + -1x = 0 + -75 Combine like terms: 75 + -75 = 0 0 + -1x = 0 + -75 -1x = 0 + -75 Combine like terms: 0 + -75 = -75 -1x = -75 Divide each side by '-1'. x = 75 Simplifying x = 75
| 3(4x+9)=75 | | 5(n-10)-7n=18 | | 2x+64=180 | | 7w^2-25=62 | | 6(3x+11)=3 | | -3x-10=6-2x | | 10x+4-2-3x=-12 | | 27+4y-9=17y-14-5y | | 7n+4=3n-8 | | 36w^2-25=62 | | 4(y+5)-3y+7=10 | | r^2-12r+35=62 | | 17x-32+24x=12 | | 2(n+1)+3(n+6)=-35 | | x=62square | | 3r^2+16r-35= | | 2(2g-3)=24 | | -5+p=-36 | | x(x-5)+(x-5)=0 | | 4=0.6s | | 11x^2-2x+9=62 | | 4n+5-2n+10=49 | | A(n)=4+(n+1)(6) | | z^5=0 | | 15.35+10.25c=425.35 | | -3(4x+3)+4(6x+1)=43+4x | | (149-3x)=(5x+12) | | 1+14i= | | 5n^2-58n+80= | | 2x-6+2x-6+x+3+x+3=26 | | 3(-x-3)=4x-2(x+1) | | 25m+.45=40m+.25 |